Energy density comparable with Li-ion batteries from aqueous supercapatteries of PANI/V2O5/SnO2 nanocomposite and its green electrolytes - Aranganathan Viswanathan; Theertha Premalatha Ramesh; Megha Naik; Adka Nityananda Shetty (Next Materials)
The PANI53.85 %: V2O534.62 %: SnO211.53 % (PVS) ternary nanocomposite synthesized by insitu synthesis as supercapattery electrode material has exhibited energy density (E) equivalent to that of Li-ion batteries as the PVS furnishes an impressive E of 114.13 W h kg1 with a high power density (P) of 2.400 kW kg1 at 2 A g1 in real 2 EL-supercapattery cell set up with low potential window (1.2 V) provided by 1 M H2SO4. The energy storage performance resulted by PVS is, a specific capacity (Q) of 684.8 C g1, at 2 A g1. The PVS is robust to withstand its energy storage characters up to 13600 cycles at 0.4 V s1. The Li-ion supercapattery device of PVS made with a green electrolyte exhibited a Q of 672.0 C g1, E of 112.0 W h kg1 and P of 1.200 kW kg1 at 1 A g1.